Implementasi Smart Integrated Garden Light Berbasis IoT: Sistem Penerangan Adaptif dengan Monitoring Mikroklimat dan Kualitas Udara untuk Area Terbuka Hijau - Rendy Pratama Sihombing; Raafiardian Sena Manu Mayoso; Roi Tua Simarmata; Eka Dodi Suryanto; Dian Putra Saragi (Kampus Akademik Publiser, 2026)
Conventional lighting systems in green open spaces, such as city parks and residential gardens, predominantly rely on manual controls or static timers. This conventional approach often leads to significant electrical energy waste, as the lights continuously operate at maximum intensity regardless of the presence of visitors or activity in the area. In addition, the increasingly urgent issue of environmental pollution necessitates the availability of microclimate monitoring data that the public can easily access prior to engaging in outdoor activities. This research aims to design and implement an Internet of Things (IoT)-based Smart Integrated Garden Light prototype as an intelligent solution that integrates energy efficiency with an environmental monitoring station. The prototype utilizes the ESP32 DevKit V1 microcontroller as the central processing unit, interfaced with four primary sensors: a Light Dependent Resistor (LDR) to detect day and night ambient lighting conditions, a Passive Infrared (PIR) sensor to detect visitor movements, a DHT11 sensor for temperature and humidity monitoring, and an MQ-135 sensor to detect fluctuations in harmful gases (air quality). The methodology employed includes literature review, hardware and software design using a multitasking approach in the Arduino IDE, physical assembly, and functional testing scenarios. Through this design, the system is expected to significantly reduce energy consumption by implementing an adaptive lighting mechanism (dimming), wherein the light will operate in a dim state (standby mode) when the park is empty at night, and automatically switch to full brightness upon detecting visitor presence. Furthermore, the system is designed to transmit microclimate parameter data continuously and in real-time to a cloud platform via the Blynk application, allowing users to transparently access environmental information using a smartphone. It is concluded that this innovation has the potential to transform garden lamp posts from mere conventional lighting devices into intelligent infrastructures (smart nodes) that support security, energy efficiency, and a sustainable Smart City concept